Al Islam and Kemuhammadiyahan Learning Innovations at SD Muhammadiyah 5 Porong during the COVID-19 Pandemic - Noor Evita Agustin; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study was to find out the innovations of Al Islam and Kemuhammadiyahan learning that were applied at SD Muhammadiyah 5 Porong during the covid-19 pandemic. In the research process this time using data collection techniques with interviews, observations, photos and videos. The results show that there are several innovations applied by educators in the teaching and learning process during the pandemic. The innovations implemented at SD Muhammadiyah 5 Porong are the presentation of learning with multimedia that utilizes the google classroom application, learning media videos and WAG, giving challenges to students and parents with the method of connecting paragraphs or letters, and implementing activity-based learning evaluations by creating independent and adaptable to new situations. The obstacles experienced during the learning process during the COVID-19 pandemic, among others, lack of understanding of ICT for parents and students, internet network problems, difficulties for educators to monitor the overall progress of students and delays in collecting assignments.